2023
DOI: 10.1002/wsb.1495
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methods to estimate feral burro abundance

Jacob D. Hennig,
Kathryn A. Schoenecker

Abstract: Obtaining precise and unbiased estimates of feral burro (Equus asinus) abundance in the western United States is challenging due to their cryptic pelage and the rugged terrain they inhabit. Management agencies employ helicopter‐based, simultaneous double‐observer sightability surveys (hereafter denoted as DOS) to estimate abundance of burros; but the DOS method routinely produces negatively biased estimates due to residual heterogeneity in detection probability. Consequently, testing alternative methods to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…An alternative is to base estimation on mark-recapture distance sampling to remove residual heterogeneity resulting from distance between the animal and sampler. Hennig and Schoenecker (2023) found that mark-recapture distance sampling was more cost-effective and less invasive for aerial surveys of wild burros than methods that included a sample of telemetered animals (Hennig et al 2022), which are similar to what we have described and recommended here. Researchers should always be cognizant of heterogeneity in detection probability in the selection and implementation of the sampling method and analysis approaches for their data.…”
Section: Research Implicationssupporting
confidence: 79%
“…An alternative is to base estimation on mark-recapture distance sampling to remove residual heterogeneity resulting from distance between the animal and sampler. Hennig and Schoenecker (2023) found that mark-recapture distance sampling was more cost-effective and less invasive for aerial surveys of wild burros than methods that included a sample of telemetered animals (Hennig et al 2022), which are similar to what we have described and recommended here. Researchers should always be cognizant of heterogeneity in detection probability in the selection and implementation of the sampling method and analysis approaches for their data.…”
Section: Research Implicationssupporting
confidence: 79%